Acute Coronary Syndrome during the Pandemic New Coronavirus Infection - O. M. Drapkina; A. Ya. Kravchenko; A. V. Budnevskiy; A. V. Kontsevaya; E. S. Ovsyannikov; E. S. Drobysheva (Рациональная фармакотерапия в кардиологии)
The experience of managing patients with COVID-19 around the world has shown that, although  respiratory symptoms predominate  during the manifestation of infection, then many patients can develop serious damage  to the cardiovascular system. However, coronary artery disease (CHD) remains the leading cause of death worldwide. The purpose of the review is to clarify the possible pathogenetic links between COVID-19 and acute coronary syndrome (ACS), taking into account which will help to optimize the management of patients with comorbid  pathology. Among the body's responses to SARS-CoV-2 infection, which increase the likelihood of developing  ACS,  the role of systemic inflammation, the quintessence  of which is a "cytokine storm" that can destabilize  an atherosclerotic  plaque is discussed.  Coagulopathy, typical for patients with Covid-19, is based on immunothrombosis, caused by a complex  interaction between neutrophilic  extracellular  traps and von Willebrandt  factor in conditions  of systemic inflammation. The implementation  of a modern strategy  for managing patients with ACS,  focused on the priority of percutaneous interventions (PCI), during  a pandemic is experiencing great  difficulties  due to the formation  of time delays  before  the start of invasive  procedures  due to the epidemiological situation. Despite this, the current European,  American and Russian recommendations for the management of infected patients with ACS confirm the inviolability of the position of PCI as the first choice for treating patients with ACS and the undesirability  of replacing  invasive treatment with thrombolysis.